Glatiramer acetate treatment normalized the monocyte activation profile in MS patients to that of healthy controls. Issue 3 (15th November 2016) - Chuluundorj, Delgertsetseg; Harding, Scott A; Abernethy, David; La Flamme, Anne Camille
Abstract : Multiple sclerosis (MS) is an immune‐mediated disease of the central nervous system, and monocytes contribute to MS‐associated neuroinflammation. While classically activated monocytes promote inflammation, type II‐activated monocytes improve the course of MS. This study investigated type II activation of monocytes and their two main subsets, namely CD14 + (CD14 ++ CD16 − subset) and CD16 + monocytes (CD14 + CD16 + subset), by glatiramer acetate (GA) or intravenous immunoglobulin‐associated immune complexes (IC), both of which are known MS treatments. Total monocytes and subsets were isolated from peripheral blood mononuclear cells (PBMC) of healthy controls, untreated MS patients (MS) and GA‐treated MS patients (GA‐MS). In contrast to the more activated ex vivo profile of monocytes from the MS group, monocytes from the GA‐MS group resembled those from healthy controls. In vitro type II activation with GA primarily reduced CD40, CD86 and IL‐12p40 whereas type II activation with IC consistently reduced CD40 but increased interleukin‐10 (IL‐10), suggesting that the GA and IC activation pathways are distinct. Moreover, while GA treatment reduced IL‐12p40 by both CD14 + and CD16 + subsets, IC treatment only enhanced IL‐10 by the CD16 + subset. Further analysis of the CD16 + subset revealed that MS patients had a greatly expanded CD14 + CD16 int population while both CD14 + CD16 int and CD14 low CD16 high monocyte populations were expanded in GA‐MS patients. Finally, a global analysis of the ex vivo monocyte data indicated that GA treatment distinctly altered the monocyte profile of MS patients, further supporting the idea that GA directly targets monocytes.